The Seed dormancy in cucumber (Cucumis sativus L.): Insights and interventions - Nagegowda, N S; H S, Dr. Yogeesha; Pitchaimuthu, M; Prashanth Kumar, G M; Dhananjaya, M V (Journal of Horticultural Sciences, 2025)
Cucumber seeds that have been freshly extracted show dormancy. In the first experiment, cucumber var. Pusa Uday seeds were subjected to various treatments viz., running with tap water, GA3, benzyl adenine, ethylene, KNO3, HNO3 and control (dry seed). The results revealed that seeds treated with benzyl adenine at 150 ppm for 12 hr recorded the highest germination (5.5%). Second experiment was carried out to find out an effective method for breaking seed dormancy and also to study how long it persists when stored under ambient conditions. When the initial trial with chemical treatments failed to break seed dormancy, the seeds were exposed to varying durations of dry heat treatment. Results revealed that seed dormancy in fresh seeds of the cucumber var. Pusa Uday could be totally overcome by a four-day dry heat treatment at 70°C without impacting other seed quality parameters. Such seeds could be stored for 24 months under ambient conditions without any reduction in viability and vigour. Additionally, it was observed that seed dormancy was naturally broken within 4 months when seeds were stored under ambient conditions, without any specific treatment.